2008
DOI: 10.1016/j.jconrel.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Efficient gene silencing in metastatic tumor by siRNA formulated in surface-modified nanoparticles

Abstract: We have developed a nanoparticle (NP) formulation for systemically delivering siRNA into metastatic tumors. The NP, composed of nucleic acids, a polycationic peptide and cationic liposome, was prepared in a self-assembling process. The NP was then modified by PEG-lipid containing a targeting ligand, anisamide, and thus was decorated for targeting sigma receptor expressing B16F10 tumor. The activity of the targeted NP was compared with the naked NP (no PEGylation) and nontargeted NP (no ligand). The delivery ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
135
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(141 citation statements)
references
References 17 publications
5
135
1
Order By: Relevance
“…Banerief et al [77] first demonstrated the use of the selective sigma ligand namely anisamide to mediate efficient targeting of liposomal drugs to sigma receptor-expressing prostate cancer cells in vitro and in vivo. Since then there have been several articles reporting the application of anisamide targeting nanoparticles for the cell specific delivery of therapeutic siRNA [78][79][80] .…”
Section: Serum Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Banerief et al [77] first demonstrated the use of the selective sigma ligand namely anisamide to mediate efficient targeting of liposomal drugs to sigma receptor-expressing prostate cancer cells in vitro and in vivo. Since then there have been several articles reporting the application of anisamide targeting nanoparticles for the cell specific delivery of therapeutic siRNA [78][79][80] .…”
Section: Serum Stabilitymentioning
confidence: 99%
“…As these ABCD formulations are nearly neutral or even negative in charge, the remarkable gene silencing data when administered systemically must be a result of active cell-specific targeting. Li and colleagues developed a nanoparticle formulation for successfully systemic delivery of siRNA into xenograft [122,80] and metastatic tumours [78,79] which produced anti-cancer effects. In this system, the nucleic acids (siRNAs and carrier DNA), a polycationic peptide (protamine) and a cationic liposome, were initially prepared in a condensed core.…”
Section: "Abcd" System -Based Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Currently available delivery vehicles lack high delivery rates upon intravenous application. Li et al 42 demonstrated specific knockdown of luciferase expression to 20-30% in a lung metastasis mouse model with B16F10 cells stably expressing luciferase. As delivery vehicle nanoparticle-formulated siRNA was …”
Section: Rcr-mediated Gene Silencingmentioning
confidence: 99%
“…Although preclinical studies in prostate cancer (16) and immune cells (17) are promising, distant tumor delivery has not been tested in the clinic. In order to mitigate this higher Peg-lipid content is used to improve the pharmacodynamic and biodistribution of LNP systems to the tumor site (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%